Exploring View of Nature of Science and Technology Pre-Service Chemistry Teachers - Devita Marlina Venessa; Hernani Hernani; Heli Siti Halimatul (Universitas Pendidikan Indonesia, 2019)
This study aims to explore the views of pre-service chemistry teachers on the nature of science and technology. Pre-service chemistry teachers’ view of nature of science and technology (VNOST) is very important to help their students later in understanding the concepts of science. This research is the initial stage in didactical design research involving 48 pre-service chemistry teachers from Sriwijaya University. The descriptive method is used to explain the results of the analysis of pre-service chemistry teachers’ VNOST. Student views were assessed using the VNOST questionnaire, consisting of 8 questions and guided by the discourse of ionic liquid technology. Data collection uses a survey containing the views of pre-service chemistry teachers on VNOST and where each statement grouped according to three categories, namely